Personal Values and Moral Disengagement Promote Aggressive and Rule-Breaking Behaviours in Adolescents With Disruptive Behaviour Disorders: A Pilot Study. (January 2017) - Paciello, Marinella; Muratori, Pietro; Ruglioni, Laura; Milone, Annarita; Buonanno, Carlo; Capo, Rosario; Lochman, John E.; Barcaccia, Barbara
The pilot study presented in this article investigated the role of moral-cognitive features in understanding aggressive and rule-breaking behaviours in adolescents with Disruptive Behaviour Disorder (DBD). We collected two samples. The community sample was composed of 85 adolescents, whereas the DBD sample was composed of 30 adolescents. Compared with a community sample, adolescents with DBD are more inclined to use moral disengagement (MD) to legitimize their aggressive and rule-breaking behaviours. Moreover, regression models showed that self-enhancement values and MD foster externalizing behaviours taking into account both gender and the group they belonged to, that is, either clinical or community sample. Instead, self-transcendence values could prevent externalizing problems by inhibiting MD. Implications of these findings for assessment and therapeutic interventions are discussed.